AL-AL'AB AL-LUGHAWIYAH FI TA'LIM AL-LUGHAH AL-'ARABIYAH FI AL-MADARIS AL-IBTIDAIYAH FI BARNAMAJ J-QAF FI MALAYSIA : DIRASAH TAHLILIYAH - Chik, Abdul Rahman (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2015)
This research aims to find out how the use of language games and their impact in the educational attainment of the primary school students in the Arabic language education in the j-QAF  program, and also aims to identify the extent of the application of the proposed model language games existing models in the textbooks. The study adopted a descriptive analytical methodology, to study and analyze the research problem, as taught in the theoretical aspect of language games model specified in the basic books of the material. In terms of analytical work side it will be implemented to identify and distribute them to teachers to poll their opinions. Find and reach the conclusion that this program a new educational program applied by some teachers using language games, and this program has a strong impact on the educational achievement of primary school students in the teaching of Arabic, Malaysia. It was found that the application of the proposed model of language games in textbooks models deemed effective.DOI: 10.15408/a.v2i2.2089